Mythische Sphärenwechsel - Zgoll, Annette; Zgoll, Christian (Mythological Studies, 2020)
Journeys to the realm of the dead, voyages to the island of souls, ascents to heaven - this book analyzes and reconstructs sphere change myth material using an innovative theoretical and methodological approach. The research strategy adopted here offers new insights into dynamic transfer processes in myths, and reveals striking evidence of various strata that result in several parallel levels of meaning.